The Sinless Children of Adam and Eve: Christ and Satan, ll. 469–83. (9th November 2018) - Hill, Thomas D; Wright, Charles D
Abstract: In the Old English poem Christ and Satan, Christ addresses the souls of the just whom he has freed from Hell, speaking of how Adam and Eve had children before the fall. There is a lacuna and a syntactically confused passage in this speech, and editors have emended the text in order to provide an approximately conventional account of the temptation and fall of Adam and Eve. Editors have generally assumed that the claim that Adam and Eve had children before the fall is a result of scribal error or authorial confusion, since children born before the fall would, by definition, be sinless. But belief in prelapsarian children of Adam and Eve is in fact affirmed in the Hiberno-Latin Reference Bible and in the Middle-Irish 'Dúan in choícat cest', and was even current in Old and Middle Irish tales dealing with the Otherworld, which make explicit their sinless condition. Editors have assumed that the ideology of Christ and Satan is conventionally 'Augustinian' Christianity but there were other strands of Christian thought in the early Middle Ages in the British Isles and in Christ and Satan, the risen triumphant Jesus tells a strikingly unconventional account of the life of Adam and Eve before the fall.